Immunization of Wistar female rats with 255-Gy-irradiated Toxoplasma gondii: Tissue parasitic load and lactogenic quantification - Camossi, Lucilene Granuzzio [UNESP]; Fornazari, Felipe [UNESP]; Richini-Pereira, Virginia Bodelao [UNESP]; Silva, Rodrigo Costa da [UNESP]; Ferreira Cardia, Daniel Fontana [UNESP]; Langoni, Helio [UNESP] (Elsevier B.V., 2015)
Toxoplasma gondii is one of the most significant parasite, due its importance in veterinary medicine and in public health, considered a food-borne pathogens, there is no available drug treatments to eliminate it from animal tissue, this reinforce the search for a vaccine against this parasite. This study was aimed to evaluate the dynamic of the distribution of T gondii in tissues of female Wistar rats and their milk, after the immunization by oral rote with irradiated tachyzoites. One week after pregnancy confirmation, rats was challenged by gavage with T. gondii bradyzoites, oocysts or tachyzoites of T. gondii. Forty-eight pregnant rats were grouped as follows: immunized and challenged with bradyzoites (BZ*); non-immunized and challenged with bradyzoites (BZ); immunized and challenged with oocysts (OC*); non-immunized and challenged with oocysts (OC); immunized and challenged with tachyzoites (TZ*); non-immunized and challenged with tachyzoites (17); only immunized (I); control group (C). After parturition, milk samples were collected for 3 weeks and then rats were sacrificed and the tissues and milk samples were researched for T gondii parasite load determined by the quantitative PCR (qPCR). It was verified that the immunization with irradiated tachyzoites of T. gondii induced the reduction of parasitic load in muscle samples in rats challenged by bradyzoites and oocysts, although not enabled the development of sterile immunity. The detection of parasite DNA in milk was found throughout the lactation period, from immunized and non-immunized rats, however no differences were found in the parasite load caused by immunization. (C) 2015 Published by Elsevier Inc.
Keywords: Toxoplasmosis; Immunization; Wistar rats; Parasite burden; Milk